Penerapan Assessment Kurikulum Merdeka Pada Pembelajaran PAI di SDN 02 Magek - Saputra, Agi; Wati, Salmi (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
In education, assessment cannot be separated and goes hand in hand and side by side. Apart from that, the existence of an independent curriculum in the world of education makes it possible to implement several new regulations regarding the evaluation of Islamic religious education for students, in order to achieve quality education. This places a great responsibility on educators. This research aims to determine the implementation of independent curriculum evaluation in PAI learning at SDN 02 Magek. The method used in this research is descriptive and qualitative. The main informant in this research was an Islamic religious education teacher and the supporting informants were the school principal and class V students who were used by the researcher as supporting informants. Next, the author uses observation, interviews and documentation methods in the data collection process. The data analysis techniques used are presentation, study and drawing conclusions. This shows that educators make a list of questions about learning material during cognitive diagnosis, even though it is not included in the educational module in a complex manner. Noncognitive diagnosticians have asked questions of educators, but rarely ask about students' activities at home or at school. Formative assessment: Educators have created Learning Goal Achievement Criteria and question grids, but although the formative assessment format based on the independent curriculum has changed, the implementation of formative assessment is still in the form of homework or school exercises so it has not changed.